JOB SATISFACTION MEMEDIASI CAREER DEVELOPMENT, PERCEIVED SUPERVISIOR SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Nala Tri Kusuma (JURNAL EKOBIS DEWANTARA, 2023)
This research is the test of the mediation of job satisfaction to the career development towardorganizational citizenship behavior, and the test of the mediation of perceived supervisiorsupport toward organizational citizenship behavior. Samples taken were 322 respondentsusing the accidental sampling. Data analysis method using multiple linear regression test andsobel test. This study found that career development has a significant positive effect jobsatisfaction, perceived supervisior support has a significant positive effect to job satisfaction,career development has a significant positive effect organizational citizenship behavior,perceived supervisior support has a significant positive effect organizational citizenshipbehavior, job satisfaction has a significant positive effect organizational citizenship behavior.The result showed that job satisfaction has a mediate career development towardorganizational citizenship behavior. The result showed that job satisfaction has a mediateperceived supervisior support toward organizational citizenship behavior.